Evaluation of online and inline emitters clogging with treated waste water and groundwater - Qadir, Niyan Jalal; Aziz, Salahaddin Abdulqadir (Sulaimani Journal for Pure and Applied Sciences, 2021)
Clogging is a serious problem in drip irrigation, especially under applied groundwater (Gw) and treated wastewater (TWW). This Clogging may uneven water distribution, and the regularity of this distribution decreases due to the emitter clogging. Laboratory tests were conducted with fresh water to evaluate the system under several applied pressures (40, 80,100,120,140,180,200 kPa) and two types of emitters (online with discharge 2 L/h and in line with discharge 8 L/h). A field experiment was also conducted from May to December 2020 at the experimental farm of the college of agricultural engineering sciences, Sulaimani University to monitor clogging of two types emitters and two types of water resources. The objectives of this study, were to evaluate the temporal changes of the emitter discharge rate and the rating of clogged emitters in the system and to quantify the effect of emitter clogging on irrigation system performance. In the experiments, two types of emitters and two types of water sources (treated wastewater and groundwater) were evaluated by measuring the emitter discharge rate of the system at seven -days intervals. Assessment time were (0, 14, 28, 42, 56, 70, and 84 hours). The water source had a very significant effect on the degree of drip emitter clogging. Of the two emitters tested during the entire trial period, emitters apply a more severe flow of Treated wastewater clogging, Results showed that the clogging percentages were 76.92% and 80.61% with inline emitter in use Groundwater and Treated wastewater and 29.76% and 26.76% with the online emitter when using Groundwater and Treated wastewater respectively.
Keywords: Wastewater; emitter clogging; groundwater; drip irrigation